Immunotherapeutic Activities of a DNA Plasmid Carrying the Mycobacterial hsp65 Gene (DNAhsp65) - Silva, Celio Lopes; Malardo, Thiago; Tahyra, Aline Seiko Carvalho (Frontiers in Medical Technology, 2020)
DNA vaccines have become a relevant subject matter and have been raising efforts for their development due to their potential as technology platforms applicable both for prevention and therapeutic treatment of infectious diseases caused by a multiplicity of pathogens as well as for the treatment of cancer, allergies and autoimmune diseases. In this review, we aimed to summarize our current knowledge about the plasmid DNA vaccine carrying the mycobacterial hsp65 protein gene (DNAhsp65), which demonstrated to display immunomodulatory and immunoregulatory properties of the innate and adaptive immune system. The possible mechanisms associated with the modulation and regulation role of DNAhsp65 in the control of various conditions will be discussed.